Law Enforcement Reform on Covid 19 Pandemic: a Necessity or an Innovation? - Andri Winjaya Laksana (Fakultas Hukum Universitas Muhammadiyah Magelang, 2020)
This study aims to identify the urgency and the form of law enforcement reform in the Covid 19 pandemic era. The approach method used is juridical normative. The type of data used in this research is secondary data consisting of primary legal materials, secondary legal materials, and tertiary legal materials. The result shows that law enforcement reform in the Covid 19 pandemic era took online trials of courts. Based on the value of justice to achieve legal certainty manifested in online trials, legal certainty in online trials in achieving justice values in criminal cases is legal. The criminal justice system reviews it since the investigation, prosecution, trial, and execution. Some legal actions can be seen from 3 (three) things: position, authority, and procedure as parameters of the action or legal action carried out at each process level case.